De novo missense variants in MEIS2 recapitulate the microdeletion phenotype of cardiac and palate abnormalities, developmental delay, intellectual disability and dysmorphic features. Issue 9 (28th July 2018) - Douglas, Ganka; Cho, Megan T.; Telegrafi, Aida; Winter, Susan; Carmichael, Jason; Zackai, Elaine H.; Deardorff, Matthew A.; Harr, Margaret; Williams, Linford; Psychogios, Apostolos; Erwin, Angelika L.; Grebe, Theresa; et al.
Abstract : Gross deletions involving the MEIS2 gene have been described in a small number of patients with overlapping phenotypes of atrial or ventricular septal defects, cleft palate, and variable developmental delays and intellectual disability. Non‐specific dysmorphic features were noted in some patients, including broad forehead with high anterior hairline, arched eyebrows, thin or tented upper lip, and short philtrum. Recently, a patient with a de novo single amino acid deletion, c.998_1000delGAA (p.Arg333del), and a patient with a de novo nonsense variant, (c.611C>G, p.Ser204*), were reported with a similar, but apparently more severe phenotypes. Clinical whole exome sequencing (WES) performed at our clinical molecular diagnostic laboratory identified four additional patients with predicted damaging de novo MEIS2 missense variants. Our patients' features closely resembled those previously reported in patients with gross deletions, but also included some less commonly reported features, such as autism spectrum disorder, hearing loss, and short stature, as well as features that may be unique to nucleotide‐level variants, such as hypotonia, failure to thrive, gastrointestinal, skeletal, limb, and skin abnormalities. All of the observed missense variants, Pro302Leu, Gln322Leu, Arg331Lys, and Val335Ala, are located in the functionally important MEIS2 homeodomain. Pro302Leu is found in the region between helix 1 and helix 2, while the other three are located in the DNA‐binding helix 3. To our knowledge, these are the first described de novo missense variants in MEIS2, expanding the known mutation spectrum of the newly recognized human disorder caused by aberrations in this gene.